Help seeking, self-efficacy, and writing performance among college students - Williams, James D.; Takaku, Seiji (Journal of Writing Research, 2011)
Adaptive help seeking and self-efficacy have been examined extensively over the last 20 years, but few studies have investigated their role in writing center tutoring, which has become an important component of process-oriented writing instruction. Using data collected over an 8-year period, this study analyzes the effect of writing self-efficacy (assessed using established self-efficacy scales) and help-seeking behavior (measured by frequency of writing center visitation) on writing performance as measured by composition grades. Participants were 671 undergraduates, approximately half of whom were international students for whom English was a second or third language. Data analyses showed an inverse correlation between self-efficacy and help-seeking behavior. In addition, high levels of help-seeking behavior resulted in better performance in composition classes, especially for the ESL participants; indeed, this behavior was the strongest predictor of success.